2006
DOI: 10.1101/lm.80206
|View full text |Cite
|
Sign up to set email alerts
|

Foreground contextual fear memory consolidation requires two independent phases of hippocampal ERK/CREB activation

Abstract: Fear conditioning is a popular model for investigating physiological and cellular mechanisms of memory formation. In this paradigm, a footshock is either systematically associated to a tone (paired conditioning) or is pseudorandomly distributed (unpaired conditioning). In the former procedure, the tone/shock association is acquired, whereas in the latter procedure, the context/shock association will prevail. Animals with chronically implanted recording electrodes show enhanced amplitude of the extracellularly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
125
2

Year Published

2007
2007
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(133 citation statements)
references
References 62 publications
(77 reference statements)
6
125
2
Order By: Relevance
“…However, the effects of nicotine withdrawal on ERK and CREB signaling in the hippocampus remain unknown. Studies have demonstrated that both ERK and CREB are involved in foreground and background contextual fear conditioning [70,73,81], and that the acute effects of nicotine on background contextual fear conditioning critically depend on ERK [68]. Thus, withdrawal-associated changes in these signaling molecules could disrupt contextual fear conditioning.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the effects of nicotine withdrawal on ERK and CREB signaling in the hippocampus remain unknown. Studies have demonstrated that both ERK and CREB are involved in foreground and background contextual fear conditioning [70,73,81], and that the acute effects of nicotine on background contextual fear conditioning critically depend on ERK [68]. Thus, withdrawal-associated changes in these signaling molecules could disrupt contextual fear conditioning.…”
Section: Discussionmentioning
confidence: 99%
“…A 3 × 3 repeated-measures ANOVA with dB (69,73,81) as the within subjects factor and drug condition (0.0, 6.3, 12.6 mg/kg/day) as the between subjects factor revealed that there was a significant within-subjects effect of pre-pulse intensity level on PPI [F(2, 35) = 35.06, p < 0.01]; higher dBs produced greater PPI. However, there was no significant overall effect of drug condition on PPI, nor was there a drug condition by pre-pulse intensity interaction (p > 0.05; Figure 2).…”
Section: The Effect Of Withdrawal From Chronic Nicotine Administratiomentioning
confidence: 99%
See 1 more Smart Citation
“…Neuronal plasticity underlying memory formation (Atkins et al, 1998;Sananbenesi et al, 2002;Trifilieff et al, 2006) and stress-induced facilitation (Sananbenesi et al, 2003;Yang et al, 2004a;Revest et al, 2005) of contextual fear involves hippocampal ERK mechanisms regulated by several upstream kinases. ERK is also required for extinction of contextual fear (Szapiro et al, 2003;Fischer et al, 2007) and shows accelerated and more robust induction as well as increased nuclear accumulation (Chen et al, 2005;Fischer et al, 2007) when compared to fear conditioning.…”
Section: Introductionmentioning
confidence: 99%
“…Like αCaMKII, all three proteins are involved in neuronal differentiation, and ERK1/2 and CREB have also been shown to play a role in LTP and memory processes (Trifilieff, 2006). E2 action has previously been linked to ERK1/2 and CREB phosphorylation in various populations of neurons and in vivo (Lee, 2004;Bryant DN, 2005;Szego, 2006), and we have provided evidence that αCaMKII action mediates their phosphorylation by E2 in NLT and primary hippocampal neurons.…”
Section: Discussionmentioning
confidence: 57%